ANALISIS SWOT (STRENGTHS, WEAKNESSES, OPPORTUNITIES, THREATS) TERHADAP PENGGUNAAN APLIKASI DIGI MOBILE BANKING BANK BJB - Larissa Inez Ardelia (2022)
This researcher aims to find out how the influence of BJB DIGI Mobile Banking on banking development, and to find out how the position of competitive advantage Strengths, Weaknesses, Opportunities, Threats (SWOT) in the BJB DIGI Mobile Banking application. It is necessary to understand the existing situation and information by looking at internal data and external data from the DIGI mobile banking service strategy. Internal factors in determining strategy in the BJB DIGI application consist of strengths and weaknesses. External factors in determining competitive strategy in the BJB DIGI mobile banking application consist of opportunities and threats. One of the strategies that can be used is to determine the strategy for the BJB DIGI mobile banking application, namely the stable growth strategy, meaning that in the SWOT analysis the use of the DIGI application uses a stable growth strategy. Based on the results of DIGI mobile banking research, to improve the quality of DIGI services, improve data security with layered security, increase the dissemination of DIGI mobile banking to customers so that customers have a better understanding of using DIGI application services.